Study of natural gas powered solid oxide fuel cell simulation and modeling - Ahmad, Nafees; Ruwaida, Abdul Rasid (IOP Publishing Ltd, 2019)
Solid oxide fuel cell (SOFC) system has been proposed to address the issue of waste gas emission due to gas flaring in oil and gas industry. System has unique advantage of consuming the waste gases and generating electricity as bye product. To analyze and quantify the proposed benefits, a robust cell performance model is highly desirable. A detailed understanding of SOFC component including electrode, electrolyte, interconnect, fuel processing and electrochemical reactions are first step in accurate determination of characteristic performance of the system. For this purpose, a review of modeling philosophies of SOFC system was undertaken in this study. Specifically, SOFC simulation and modeling using commercial software such as Aspen Plus, Aspen Hysys was focused in detail. SOFC models available in literature are either mathematical model or numerical models and ever evolving and improving. SOFC simulation rely on split approach due to absence of built-in module. Authors have developed an Aspen Hysys simulation model using split approach and discussed briefly here. Split approach approximates the SOFC phenomena, thereby inducing error. To overcome this deficiency, authors are developing a MATLAB based user model that can be integrated using 'user unit operation' available in Hysys. Details of the MATLAB program approach is included.